Human Subject Research for Engineers A Practical Guide - de Winter, Joost C.F; Dodou, Dimitra (SpringerBriefs in Applied Sciences and Technology, 2017)
This Brief introduces engineers to the main principles in ethics, research design, statistics, and publishing of human subject research. In recent years, engineering has become strongly connected to disciplines such as biology, medicine, and psychology. Often, engineers (and engineering students) are expected to perform human subject research. Typical human subject research topics conducted by engineers include human-computer interaction (e.g., evaluating the usability of software), exoskeletons, virtual reality, teleoperation, modelling of human behaviour and decision making (often within the framework of 'big data' research), product evaluation, biometrics, behavioural tracking (e.g., of work and travel patterns, or mobile phone use), transport and planning (e.g., an analysis of flows or safety issues), etc. Thus, it can be said that knowledge on how to do human subject research is indispensable for a substantial portion of engineers. Engineers are generally well trainedin calculus and mechanics, but may lack the appropriate knowledge on how to do research with human participants. In order to do high-quality human subject research in an ethical manner, several guidelines have to be followed and pitfalls have to be avoided. This book discusses these guidelines and pitfalls. The aim is to prepare engineers and engineering students to carry out independent research in a responsible manner.